Solve for y 5/6+1/3y=2y

Math
56+13y=2y
Combine 13 and y.
56+y3=2y
Move all terms containing y to the left side of the equation.
Tap for more steps…
Subtract 2y from both sides of the equation.
56+y3-2y=0
To write -2y as a fraction with a common denominator, multiply by 33.
56+y3-2y⋅33=0
Combine -2y and 33.
56+y3+-2y⋅33=0
Combine the numerators over the common denominator.
56+y-2y⋅33=0
Simplify each term.
Tap for more steps…
Simplify the numerator.
Tap for more steps…
Factor y out of y-2y⋅3.
Tap for more steps…
Raise y to the power of 1.
56+y1-2y⋅33=0
Factor y out of y1.
56+y⋅1-2y⋅33=0
Factor y out of -2y⋅3.
56+y⋅1+y(-2⋅3)3=0
Factor y out of y⋅1+y(-2⋅3).
56+y(1-2⋅3)3=0
56+y(1-2⋅3)3=0
Multiply -2 by 3.
56+y(1-6)3=0
Subtract 6 from 1.
56+y⋅-53=0
56+y⋅-53=0
Move -5 to the left of y.
56+-5⋅y3=0
Move the negative in front of the fraction.
56-5y3=0
56-5y3=0
56-5y3=0
Subtract 56 from both sides of the equation.
-5y3=-56
Multiply both sides of the equation by -35.
-35⋅(-5y3)=-35⋅(-56)
Simplify both sides of the equation.
Tap for more steps…
Simplify -35⋅(-5y3).
Tap for more steps…
Cancel the common factor of 3.
Tap for more steps…
Move the leading negative in -35 into the numerator.
-35⋅(-5y3)=-35⋅(-56)
Move the leading negative in -5y3 into the numerator.
-35⋅-5y3=-35⋅(-56)
Factor 3 out of -3.
3(-1)5⋅-5y3=-35⋅(-56)
Cancel the common factor.
3⋅-15⋅-5y3=-35⋅(-56)
Rewrite the expression.
-15⋅(-5y)=-35⋅(-56)
-15⋅(-5y)=-35⋅(-56)
Cancel the common factor of 5.
Tap for more steps…
Factor 5 out of -5y.
-15⋅(5(-y))=-35⋅(-56)
Cancel the common factor.
-15⋅(5(-y))=-35⋅(-56)
Rewrite the expression.
-1⋅(-y)=-35⋅(-56)
-1⋅(-y)=-35⋅(-56)
Multiply.
Tap for more steps…
Multiply -1 by -1.
1⋅y=-35⋅(-56)
Multiply y by 1.
y=-35⋅(-56)
y=-35⋅(-56)
y=-35⋅(-56)
Simplify -35⋅(-56).
Tap for more steps…
Cancel the common factor of 3.
Tap for more steps…
Move the leading negative in -35 into the numerator.
y=-35⋅(-56)
Move the leading negative in -56 into the numerator.
y=-35⋅-56
Factor 3 out of -3.
y=3(-1)5⋅-56
Factor 3 out of 6.
y=3⋅-15⋅-53⋅2
Cancel the common factor.
y=3⋅-15⋅-53⋅2
Rewrite the expression.
y=-15⋅-52
y=-15⋅-52
Cancel the common factor of 5.
Tap for more steps…
Factor 5 out of -5.
y=-15⋅5(-1)2
Cancel the common factor.
y=-15⋅5⋅-12
Rewrite the expression.
y=-1⋅-12
y=-1⋅-12
Move the negative in front of the fraction.
y=-1⋅(-12)
Multiply -1(-12).
Tap for more steps…
Multiply -1 by -1.
y=1(12)
Multiply 12 by 1.
y=12
y=12
y=12
y=12
The result can be shown in multiple forms.
Exact Form:
y=12
Decimal Form:
y=0.5
Solve for y 5/6+1/3y=2y

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top